Pemanfaatan Konseling Online Pada Guru SD Di Kalimantan Tengah - Berkat Berkat; Bhayu Rhama; Wahyuni Christiany Martono; Elisabeth Fransisca Saragi Sitio; Ferry Setiawan; Ahmad Saefulloh (STMIK Royal, 2021)
Abstract.: The current covid-19 pandemic season pays special attention to students who study at home through online methods. The thing of concern is the frequent occurrence of violence in elementary school age children while studying due to the limitation of parents as substitute teachers during online learning. Parents of students with all their activities are required to help and assist their children in making school work. So the phenomenon that occurs in the field is the uncontrolled control of parental emotions towards children, so that online learning seems to be a frightening specter for elementary students. The purpose of implementing this Online Counseling Guidance is to provide insight to elementary school teachers who are members of the Indonesian Teachers Association (PGRI) Central Kalimantan regarding the mechanism for utilizing counseling which can be done online through the Competency Assessment and Career Development Service Center (PPAKPK) web. The method of implementing this service is carried out online through Conference Via Zoom and tutorials on using the web on a YouTube account which are distributed to Bimtek participants. The results obtained at this Bimtek show that all Bimtek participants are interested in the use of Online Counseling to serve as a means of consulting both students to teachers or guardians of students to teachers or teachers to psychiatrists who can be contacted when the teacher needs student problem solving.Keywords: online counseling; elementary school teacher; central kalimantan Abstrak: Musim pandemi covid-19 saat ini memberi perhatian khusus bagi para siswa yang belajar di rumah melalui metode daring. Hal yang menjadi perhatian adalah sering terjadinya kekerasan pada anak usia SD saat belajar dikarenakan faktor keterbatasan orang tua sebagai guru pengganti selama pembelajaran daring. Orang tua siswa dengan segala kesibukannya dituntut untuk membantu dan mendampingi anak-anak mereka membuat Pekerjaan Sekolah. Maka fenomena yang terjadi di lapangan adalah pengendalian emosi orang tua yang tidak terkendali kepada anak, sehingga pembelajaran daring terkesan menjadi momok yang menakutkan bagi para siswa SD. Tujuan dari pelaksanaan Bimtek Konseling Online ini adalah untuk memberikan wawasan kepada para Guru SD yang tergabung di dalam Persatuan Guru Republik Indonesia (PGRI) Kalimantan Tengah terkait mekanisme pemanfaatan konseling yang dapat dilakukan secara daring melalui web Pusat Pelayanan Asesmen Kompetensi dan Pengembangan Karir (PPAKPK). Metode pelaksanaan pengabdian ini dilakukan dengan cara daring melalui Conference Via Zoom dan tutorial penggunaan web pada akun youtube yang dibagikan kepada para peserta Bimtek. Hasil yang diperoleh pada Bimtek ini menunjukan bahwa seluruh peserta Bimtek tertarik dengan pemanfaatan Konseling Online untuk dijadikan sebagai sarana konsultasi baik siswa kepada guru ataupun wali murid kepada guru ataupun Guru kepada ahli Psikiater yang dapat dihubungi saat Guru membutuhkan pemecahan masalah siswa.Kata Kunci: konseling online; guru sd; kalimantan tengah